PENGARUH SUBSTITUSI TEPUNG LABU KUNING TERHADAP SIFAT ORGANOLEPTIK DAN KADAR SERAT COOKIES SEBAGAI KUDAPAN UNTUK REMAJA 13 - 15 TAHUN - Rafa Amalia Fauzi, (2020)
Nutritional deficiency is prone to occur in adolescents. The number prevalance of fiber deficiency to teenagers is high about ≥70%. Food that has high fiber content is yellow pumpkin. The purpose of this study was to determine the effect of yellow pumpkin as wheat flour substitution on organoleptic properties, fiber content and nutritional. This study used an experimental method with a completely randomized design (CRD). This study has three formulas with each percentage level of yellow pumpkin flour as wheat substitution by F1 (16%), F2 (20%), F3 (24%). Organoleptic analysis performed used the Kruskal Wallis test and followed to the Mann Whitney test. Analysis fiber content is analyzed with ANOVA, continued with the Duncan test. The effect substitution of pumpkin flour level had a significant effect (p<0,05) on panelists preference for taste, odor and fiber content of cookies. The selected formula is F1 cookies having water content of (7,25%), ash content (1,75%), protein content (6,54%), fat content (26,4%), carbohydrate content (58%) and fiber content (11,22%).